Evaluation of the Information System (Smart Deer System) at BKPSDMD of Bangka Belitung Islands Province - Ahmad Fauzi, Aditya (Indonesian Journal of Data Science, IoT, Machine Learning and Informatics, 2025)
Improving the quality of human resources (HR) is one of the important factors in the development of a region. To realize superior, competent, intelligent, and educated human resources, a fast, easy, and useful information system is needed in the management of further education in the BKPSDMD Prov. BaBel, therefore, introduced an information system called "SI Pelanduk Cerdik" which aims to make it easier for State Civil Apparatus (ASN) in the process of submitting competency development. Therefore, the purpose of this research is as feedback to correct the shortcomings of the "SI Pelanduk Cerdik" application. The qualitative description method is the method used in this study. The results of the study show that the use of "Si Pelanduk Cerdik" in BKPSDMD Prov. BaBel is very useful. This application makes it easier for ASN in the process of submitting competency development, with quick and easy access anytime and anywhere. The level of satisfaction of ASN with this application is also very high. Before this application, the process of applying for further education by ASN was manual and time-consuming. However, with the existence of the "SI Pelanduk Cerdik", the time needed for ASN to apply for competency development can be significantly reduced, in just about 30 minutes. The app lives up to the desired expectations